2015
DOI: 10.3329/bjms.v14i1.21559
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of overweight, obesity and metabolic variables among students of a private medical college in Dhaka city

Abstract: Background: Overweight and obesity are recognized as recent threat which affecting both developing and developed countries. Obesity and its associated morbidities are leading cause of most non-communicable diseases. Few recent studies have indicated the presence of increase in overweight and obesity among children and adolescent but there is no study among adult groups. Method and material: This cross sectional study was done to assess the prevalence of overweight, obesity and metabolic variables with their re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Notably, we found that the majority of students who suffered from high BP actually had pre-HTN. Higher BP in males compared to females was also observed in a study conducted in Bangladeshi private medical students [39]. In a study conducted among the students of a central university in West Bank, around one quarter of the students had reported to be prehypertensive whereas HTN was evident in 2.2% with males being significantly more affected than females [31].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Notably, we found that the majority of students who suffered from high BP actually had pre-HTN. Higher BP in males compared to females was also observed in a study conducted in Bangladeshi private medical students [39]. In a study conducted among the students of a central university in West Bank, around one quarter of the students had reported to be prehypertensive whereas HTN was evident in 2.2% with males being significantly more affected than females [31].…”
Section: Discussionmentioning
confidence: 57%
“…The overall percentage of generalized obesity (BMI≥25 kg/m 2 ) was 20.82% in all subjects (20.09% in males and 21.58% in females). Higher prevalence of obesity among females at undergraduate medical level was also reported in Bangladesh [39]. By contrast, Yasin et al [31] reported the lower rate of obesity in girls (4%) than boys (9.4%) with an overall proportion of 7.2%.…”
Section: Discussionmentioning
confidence: 82%